Sex‐specific associations of asthma acquisition with changes in DNA methylation during adolescence. Issue 2 (25th November 2020) - Patel, Rutu; Solatikia, Farnaz; Zhang, Hongmei; Wolde, Alemayehu; Kadalayil, Latha; Karmaus, Wilfried; Ewart, Susan; Arathimos, Ryan; Relton, Caroline; Ring, Susan; Henderson, Alexander John; Arshad, Syed Hasan; et al.
Summary: Background: Underlying biological mechanisms involved in sex differences in asthma status changes from pre‐ to post‐adolescence are unclear. DNA methylation (DNAm) has been shown to be associated with the risk of asthma. Objective: We hypothesized that asthma acquisition from pre‐ to post‐adolescence was associated with changes in DNAm during this period at asthma‐associated cytosine‐phosphate‐guanine (CpG) sites and such an association was sex‐specific. Methods: Subjects from the Isle of Wight birth cohort (IOWBC) with DNAm in blood at ages 10 and 18 years (n = 124 females, 151 males) were studied. Using a training‐testing approach, epigenome‐wide CpGs associated with asthma were identified. Logistic regression was used to examine sex‐specific associations of DNAm changes with asthma acquisition between ages 10 and 18 at asthma‐associated CpGs. The ALSPAC birth cohort was used for independent replication. To assess functional relevance of identified CpGs, association of DNAm with gene expression in blood was assessed. Results: We identified 535 CpGs potentially associated with asthma. Significant interaction effects of DNAm changes and sex on asthma acquisition in adolescence were found at 13 of the 535 CpGs in IOWBC ( P ‐values <1.0 × 10 −3 ). In the replication cohort, consistent interaction effects were observed at 10 of the 13 CpGs. At 7 of these 10 CpGs, opposite DNAm changes across adolescence were observed between sexes in both cohorts. In both cohorts, cg20891917, located on IFRD1 linked to asthma, shows strong sex‐specific effects on asthma transition ( P ‐values <.01 in both cohorts). Conclusion and clinical relevance: Gender reversal in asthma acquisition is associated with opposite changes in DNAm (males vs females) from pre‐ to post‐adolescence at asthma‐associated CpGs. These CpGs are potential biomarkers of sex‐specific asthma acquisition in adolescence.